Medicine in Context: ten years’ experience in diversity education for medical students in Greater Western Sydney, Australia - Marjadi, Brahmaputra; Mapedzahama, Virginia; Rogers, Gayle; Donnelly, Margaret; Harris, Anne; Donadel, Dale; Jakstas, Emilie; Dune, Tinashe; Lo, Winston; Micheal, Sowbhagya; McKnight, Trelawny; Hennessy, Annemarie; et al. (GMS Journal for Medical Education, 2020)
Objective: This paper describes the Western Sydney University School of Medicine (WSUSoM) diversity education program, Medicine in Context (MiC). MiC implements community-engaged learning and partnership pedagogy in teaching diverse social determinants of health to first clinical year medical students. Central to MiC content and delivery methods is the local region’s diversity which is also reflected in the student population and MiC staff.Methodology: This is a descriptive report about how the WSUSoM staff with community and General Practice (GP) partners have co-designed, co-delivered, co-assessed and co-evaluated the MiC program in 2009-2018. In keeping with the community-engaged learning and partnership pedagogy, the report is co-authored by a cross section of MiC stakeholders: the WSUSoM staff members, community partners and an alumna.Results: Ten weeks' immersion in community-based services, with debriefing and scaffolding in tutorials and workshops, exposes students to the complex interplay between social determinants of health and clinical practice. Sharing of experiences, insights and reflections in safe environments enables students to overcome the uneasiness of diversity education. Quality assurance reviews identified positive trends in students’ quality of learning and satisfaction in the program following evidence-based continuous improvements of the program design and delivery. Conclusion: Implementation of community-engaged learning and partnership pedagogy in the MiC program, supported by ongoing commitment from the WSUSoM and its community and GP partners, has been successful in engaging students in diversity education. The synthesis of diversity education and clinical learning throughout the MiC program is an important step toward building competency in patient-centred care.